LESS IS MORE: THE EFFECTS OF CHILDREN ON PARENTS' INCOME, ASSETS AND INTERGENERATIONAL TRANSFERS. (11th November 2018) - Tian, L
Abstract: This dissertation examines whether having more children makes Chinese parents better off economically later in life. While more children can provide more support, children are expensive and can deplete resources because they take up both money and time. However, little is known the causal relationship between the number of children and parents' long-term income and wealth. Most studies neglected certain parents' characteristics influencing both the number of children and resources later in life, i.e. endogeneity. None analyzed the complete picture of elderly economic resources. The present study addressed endogeneity by using a better composite measure of exposure to the FPP as an instrumental variable (IV) for the number of children and used the 2011 China Health and Retirement Longitudinal Study (CHARLS) data for analysis. The IV estimates suggest that each additional child reduced parents' income by 77% and 90%, and reduced assets by 147% and 41% for rural and urban parents, respectively. These negative effects were partly offset by increased intergenerational transfers from children by 200% and 212% for rural and urban parents who had one more child, respectively. However, overall, having an additional child led to a decrease of 8, 971 and 27, 960 RMB Yuan in combined income, assets and transfers for the average rural and urban parents, respectively. The study results indicate that researchers should pay more attention to the fact that children cost money rather than focusing only on children's impact on intergenerational transfers when studying impacts of children on elderly's economic well-being.